FREQUENCY OF INSULIN RESISTANCE IN PATIENTS OF POLYCYSTIC OVARY SYNDROME - Majida Farooq (Army Medical College Rawalpindi, 2019)
Objective: The objective of this study was to determine frequency of insulin resistance (IR) in patients of polycystic ovary syndrome.